2011
DOI: 10.1080/09593330.2010.536783
|View full text |Cite
|
Sign up to set email alerts
|

Competitive adsorption of phenolic compounds from aqueous solution using sludge‐based activated carbon

Abstract: Preparation of activated carbon from sewage sludge is a promising approach to produce cheap and efficient adsorbent for pollutants removal as well as to dispose of sewage sludge. The first objective of this study was to investigate the physical and chemical properties (BET surface area, ash and elemental content, surface functional groups by Boehm titration and weight loss by thermogravimetric analysis) of the sludge-based activated carbon (SBAC) so as to give a basic understanding of its structure and to comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(26 citation statements)
references
References 45 publications
0
26
0
Order By: Relevance
“…Thus, adsorption of phenolic compounds on AC might be affected by the characteristic properties of phenolic polarity and stereospecific structure (29,30). AC is mainly hydrophobic and has a strong affinity for phenolic compounds with lower water solubility values (31). It was previously reported that hydrophobic compounds were adsorbed on AC to a greater extent than less hydrophobic compounds (32).…”
Section: Loss Of Phenolic Compounds By Reaction With Acmentioning
confidence: 98%
“…Thus, adsorption of phenolic compounds on AC might be affected by the characteristic properties of phenolic polarity and stereospecific structure (29,30). AC is mainly hydrophobic and has a strong affinity for phenolic compounds with lower water solubility values (31). It was previously reported that hydrophobic compounds were adsorbed on AC to a greater extent than less hydrophobic compounds (32).…”
Section: Loss Of Phenolic Compounds By Reaction With Acmentioning
confidence: 98%
“…Schematic representation of possible mechanism of QDs based photodegradation of organic dyes. adsorbate molecules from the bulk liquid phase into the adsorbent surface is presumed to involve the following stages [60,61]:…”
Section: Possible Mechanism and Adsorption Isothermsmentioning
confidence: 99%
“…Further decrease in pH, the quantity of undissociated phenol increases, this implies to the decrease in the interaction between phenol and the adsorbent. At a value of pH > 8, the PCP act as anions and this accompanies by a decrease in the adsorption between the negative charged phenoxy ion and the negative charge present on the surface of the adsorbent [24,25].…”
Section: Fig 5 Pore Size Distribution For the Tested Carbon Materialsmentioning
confidence: 99%